Architectural Design of 3D Printed Scaffolds Controls the Volume and Functionality of Newly Formed Bone. Issue 1 (7th December 2018) - Entezari, Ali; Roohani, Iman; Li, Guanglong; Dunstan, Colin R.; Rognon, Pierre; Li, Qing; Jiang, Xinquan; Zreiqat, Hala
Abstract: The successful regeneration of functional bone tissue in critical‐size defects remains a significant clinical challenge. To address this challenge, synthetic bone scaffolds are widely developed, but remarkably few are translated to the clinic due to poor performance in vivo. Here, it is demonstrated how architectural design of 3D printed scaffolds can improve in vivo outcomes. Ceramic scaffolds with different pore sizes and permeabilities, but with similar porosity and interconnectivity, are implanted in rabbit calvaria for 12 weeks, and then the explants are harvested for microcomputed tomography evaluation of the volume and functionality of newly formed bone. The results indicate that scaffold pores should be larger than 390 µm with an upper limit of 590 µm to enhance bone formation. It is also demonstrated that a bimodal pore topology—alternating large and small pores—enhances the volume and functionality of new bone substantially. Moreover, bone formation results indicate that stiffness of new bone is highly influenced by the scaffold's permeability in the direction concerned. This study demonstrates that manipulating pore size and permeability in a 3D printed scaffold architecture provides a useful strategy for enhancing bone regeneration outcomes. Abstract : Architecture of a 3D printed ceramic scaffold plays a prominent role in bone regeneration outcome. The present in vivo study demonstrates the critical effect of scaffolds' permeability on functionality of newly formed bone. Moreover, it is demonstrated that the bimodal pore topology in scaffolds can substantially enhance the volume of new bone.